Utilization of post-tin mining land for porang (Amorphaphillus oncophyllus) cultivation by application of cow manure compost - Inonu, Ismed; Pratama, Deni; Irwanto, Riko; Ningsih, Kurniahayati Utami (Journal of Degraded and Mining Lands Management, 2023)
Tailing post-tin mining land has a sandy textured and loose structure. Those physical properties can affect the efficiency of fertilization and cause inefficiency of nutrient absorption in plants. That issue can be corrected by the application of organic material such as cow manure compost which has the potential for plant cultivation, especially for â€œporangâ€ (Amorphaphillus oncophyllus Prain). This study aimed to examine the cultivation of porang plants in post-tin mining tailings by applying cow manure compost and to determine the best dose of cow manure compost for porang cultivation in artificial ex-tin mining land. This study used a single-group randomized design method with the treatment factor being the dose of cow manure compost consisting of five dose levels (5 t ha-1, 10 t ha-1, 15 t ha-1, 20 t ha-1, and 25 t ha-1). Each treatment level was replicated with five replications, and each replication consisted of five populations so the total population was 125 plants. The results showed that the application of various doses of cow manure compost to artificial post-tin mining land affected the growth and yield of porang plants. The treatment of cow manure compost at a dose of 25 t ha-1 gave the best growth and yield of porang plants. Heavy metal (Pb) analysis on porang tubers showed that all doses of cow manure compost had a Pb content value of <0.059%, which means that cow manure compost can reduce heavy metal uptake in porang tubers. Porang planted in artificial post-tin mining land is safe for consumption because lead (Pb) content was below the threshold of Indonesia National Standard (SNI) for food.